Guanylate-Binding Protein 1 Promotes Migration and Invasion of Human Periodontal Ligament Stem Cells - Shi Bai; Tao Chen; Xia Deng (Stem Cells International)
Mesenchymal stem/stromal cells (MSCs) are capable of migrating to sites of injury and inflammation in response to various cytokines to improve tissue repair. Previous studies have shown interferon-gamma (IFN-γ) promoted migration of the V54/2 cell line and dental pulp stem cells (DPSCs), but the underlying mechanisms remain largely unknown. In this study, we found IFN-γ induced migration and invasion of periodontal ligament stem cells (PDLSCs) in a dose-dependent manner in vitro. While knockdown of guanylate-binding protein 1 (GBP1) suppressed IFN-γ-induced migration and invasion, ectopic expression of GBP1 potentiated IFN-γ-induced migration and invasion of PDLSCs. Furthermore, we demonstrated GBP1 was required for IFN-γ-induced processing of matrix metallopeptidase 2 (MMP2) in PDLSCs. Our findings indicate that GBP1 promotes IFN-γ-induced migration and invasion of PDLSCs by MMP2, and GBP1 may serve as a new target to facilitate MSC homing and migration.